2021
DOI: 10.3892/or.2021.8166
|View full text |Cite
|
Sign up to set email alerts
|

Targeting USP22 with miR‑30‑5p to inhibit the hypoxia‑induced expression of PD‑L1 in lung adenocarcinoma cells

Abstract: Lung cancer is one of the most common forms of cancer and accounts for a significant proportion of all cancer-related deaths. Lung adenocarcinoma (LUAD) accounts for approximately 40% of all cases of lung cancer. In recent years, new developments in both the diagnosis and treatment of LUAD have been achieved. Unfortunately, the prognosis remains poor for patients with malignant LUAD. Hypoxia is a common characteristic of solid tumors and induce the immune evasion by increasing the expression of programmed cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…But, lung cancer detection is inadequate, with no effective treatment for metastatic or potentially metastatic lung cancer. LUAD, a lung cancer histological subtype with the highest prevalence, has a poor prognosis and occupies 40 % of the entire lung cancer patients [ 52 ]. LUAD includes many histological subtypes, among which the 5-year DFS for MIP-predominant LUAD is 0 % [ 12 ] and the OS is significantly worse in tumors with even 1 % MIP pattern [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…But, lung cancer detection is inadequate, with no effective treatment for metastatic or potentially metastatic lung cancer. LUAD, a lung cancer histological subtype with the highest prevalence, has a poor prognosis and occupies 40 % of the entire lung cancer patients [ 52 ]. LUAD includes many histological subtypes, among which the 5-year DFS for MIP-predominant LUAD is 0 % [ 12 ] and the OS is significantly worse in tumors with even 1 % MIP pattern [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we analyzed and predicted by bioinformatics means that there were potential binding sites between MANCR and miRNA-30d-5p. miRNA-30d-5p has been elucidated as a potential biomarker for the treatment of various cancers, including LUAD, prostate cancer, and gallbladder cancer [45][46][47]. It has been shown that silencing miRNA-30d-5p expression can reduce the percentage of CD8 + T cells, which leads to immune escape of prostate cancer [48].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-92a was previously confirmed to be significantly up-regulated in various cancers and to contribute to tumor progression by targeting the FBXW7 protein, which is a critical tumor suppressor and one of the most important molecules involved in the ubiquitin–proteasome system [ 56 , 57 ]. On the contrary, miR-30e-5p functions as an important inhibitor of cancerogenesis by targeting ubiquitin-specific peptidase 22 (USP22), which is a part of the SAGA complex involved in protein deubiquitination, cell cycle regulation and chromatin organization, and is highly expressed in brain tissue [ 58 , 59 ]. Altogether, these results indicate that down-regulated levels of miR-26a-5p and miR-30e-5p together with up-regulated levels of miRNAs from the miR-17-92 cluster may play an important role in the pathogenesis of EMD and its progression from MM.…”
Section: Discussionmentioning
confidence: 99%